First Ultra High Energy Neutrino Search with a Hybrid Phased and Traditional Detector in the Askaryan Radio Array - Ali,S; Besson,DZ; Alden,N; Allison,P; Archambault,S; Beatty,JJ; Bishop,A; Chen,P; Chen,YC; Chen,YC; Chiche,S; Clark,BA; et al. (2025)
The Askaryan Radio Array (ARA) is an in-ice ultrahigh energy (UHE, >10 PeV) neutrino experiment at the South Pole, designed to detect neutrino-induced radio emission in ice. It consists of five independent stations, each featuring a cubic lattice of in-ice antenna clusters spaced 30 m apart and buried 200 m below the surface. The fifth ARA station (A5) is unique due to its central phased array string, which employs an interferometric trigger to enhance sensitivity to weak signals otherwise buried in noise. This low-threshold trigger makes ARA the first in-ice radio neutrino experiment to demonstrate a significant improvement in detecting low signal-to-noise ratio (SNR) radio signals. We present progress toward the first UHE neutrino search utilizing A5’s hybrid detection capability, incorporating advancements in data selection and background rejection. This analysis is the first to fully apply dedicated event selection to both components of ARA’s hybrid detector, improving directional reconstruction and significantly enhancing background rejection compared to previous analyses. This approach paves the way for next-generation in-ice UHE neutrino experiments.